Examining High-Tech Assistive Technology Use of Students With Visual Impairments. (July 2022) - Tuttle, Michael; Carter, Erik W.
Introduction: "High-tech" assistive technology (AT) plays a critical role in the lives and educational experiences of students with visual impairments (i.e. those who are blind or have low vision). However, little is known about how these students actually use AT within their educational programs.Methods: A survey examining AT use and services among 51 students with visual impairments addressed their personal characteristics, device characteristics, device usage, AT assessment, and AT instruction. In addition, 12 teachers provided perspectives on their district's AT services and policies.Results: Students primarily used commercially available AT to access print. Some variations in use were found between elementary and secondary students. Instruction of devices was highly aligned with students' device use.Discussion: High-tech AT can meet diverse needs among students with visual impairments. Individualization of AT selection and services remains essential.Implications for Practitioners: Educators should consider AT for a broad range of student needs, promote device use at home, reflect on their instruction, and pursue professional development in this area.